Evaluation of Safety and Efficacy of Traction, Closed Reduction, and Subsequent Hip Fixation in Hilgenreiner Brace in Patients with Severe Forms of Hip Developmental Dysplasia - Ahmad Gharaibeh; Rastislav Sepitka; Jan Pobeha; Daniela Schreierova; Martina Habinakova; Gabriel Vasko; Marek Lacko (Advances in Orthopedics)
Background. Hilgenreiner brace (Hb) was developed to improve hip reduction rate and reduce the incidence of femoral head avascular necrosis (AVN). In children under the age of 18 months with unstable hip joints or a dislocated hip joint, the treatment method involves nonsurgical treatment in most cases. Objectives. To evaluate the effectiveness and safety of traction, closed reduction, and hip fixation in Hb in patients with severe forms of hip developmental dysplasia (DDH) in follow-up. Materials and Methods. Prospective, clinical, cohort observation and retrospective matched-pair analysis. Analysis of medical records was conducted to evaluate the effectiveness of using Hb for treatment of dislocated hip joints in <18-month-old children. The investigated cases were of the dislocated hip joint since DDH was confirmed through clinical and imaging diagnosis and treated by the application of the close reduction method together with Hb, in a nonhuman position (hip joint in 90 degrees of flexion and 80 degrees of abduction). Analysis was carried out using the modified Berkeley’s Mckay criteria and hip joint centralization, and evaluation was done using X-ray images according to the basic modified Severin classification system. Results. The use of Hb applied after overhead traction to (mean 22.8 days, confidence level (95%)) 68 hip joints showed a significant improvement (92%) in the treated hips. In summary, only one brace replacement was performed due to swelling of the thigh and fixation pressure, three cases suffered from hip joint redislocation after removing the Hb (5%), and one patient had bilateral avascular necrosis (2.8%). Conclusions. The use of Hb reduced avascular necrosis of the femur head, maintained higher hygiene conditions, and lowered both the risk of cast breakage and skin complications over the use of hip spica as compared to Hb. Hb is more cost-effective, and radiolucency is an additional advantage for this technique. Closed reduction and application of Hb after oral administration of a bolus dose of chlorpromazine chloride or phenobarbital resulted in complication avoidance of total anaesthesia.